Sensitivity of Phytophthora infestans to aqueous extracts of Lippia origanoides and Origanum vulgare - Burbano-David, Diana (2021)
Introduction. Phytophthora infestans (Mont.) De Bary, is considered the causative agent of one of the most devastating and limiting diseases of potato crops (Solanum tuberosum L.) in the Nariño department (Colombia). This disease is controlled using systemic fungicides, which have a negative impact on the environment and increase production costs, however, there are alternatives like the organic fungicides, which are based on the use of plant extracts with anti-fungal properties for the control of the pathogen. Objective. To evaluate aqueous extracts of O. vulgare and L. origanoides for the control of P. infestans under in vitro conditions. Materials and methods. This research was carried out in the Microbiology laboratory of the research group in Genetics and Evolution of Tropical Organisms (GENPAT) of the Universidad de Nariño, during 2017. The in vitro sensitivity of P. infestans against extracts of botanical species Lippia origanoides (wild oregano) and Origanum vulgare (common oregano) was evaluated. Results. The data obtained allowed the establishment of the base line of behavior of the pathogen populations against the evaluated compounds, there was a gradual reduction in both the growth and sporulation when the Lippia origanoides extract was used and that this same has the capacity to control the pathogen in concentrations of 100 mg ml-1. With the use of Origanum vulgare the P. infestans isolates showed different levels of sensitivity to the compound with low levels of inhibition and high values of EC-50. Conclusion. The P. infestans isolates presented different levels of sensitivity against the two aqueous extracts evaluated, with a reduction of 100 % in the inhibition radial growth and sporulation from the concentration of 100 mg ml-1, when the extract was used of L. origanoides.